2016
DOI: 10.4172/2472-4971.1000115
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Glioblastoma: A Case Report and Review of the Literature

Abstract: Glioblastoma, the most common and aggressive primary glial tumor, has a median survival time of approximately 3 months without medical treatment. Surgical resection, radiotherapy, and chemotherapy are the main methods of treatment and have been shown to increase life expectancy 1 to 2 years. The tumor has an infiltrative growth pattern that distorts the normal anatomy and can extend to distant parts of the brain along white matter tracts. While glioblastoma commonly infiltrates surrounding brain tissue and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…The presence of common GBM events such as homozygous deletion of CDKN2A, TP53 LOH, 9p loss, high mutational overlap with intracranial gliomas, and positive GFAP staining on histology sections provide strong evidence that the metastasis was derived from the intracranial gliosarcoma, rather than developing independently. The rarity of cases with extracranial metastases inhibits the elucidation of mechanisms underlying metastatic potential, but studies have suggested that physical barriers inherent to the intracranial environment, such as the dura mater, blood-brain barrier, and limited access to systemic circulation, contribute to the low occurrence of this phenomenon (Harrison et al 2016;Rosen et al 2018). Surgical intervention has been implicated as a causative factor in extracranial metastases (Beaumont et al 2007;Kalokhe et al 2012;Harrison et al 2016), but the findings of this study suggest the metastatic behavior observed was inherent to the disease progression rather than induced by therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of common GBM events such as homozygous deletion of CDKN2A, TP53 LOH, 9p loss, high mutational overlap with intracranial gliomas, and positive GFAP staining on histology sections provide strong evidence that the metastasis was derived from the intracranial gliosarcoma, rather than developing independently. The rarity of cases with extracranial metastases inhibits the elucidation of mechanisms underlying metastatic potential, but studies have suggested that physical barriers inherent to the intracranial environment, such as the dura mater, blood-brain barrier, and limited access to systemic circulation, contribute to the low occurrence of this phenomenon (Harrison et al 2016;Rosen et al 2018). Surgical intervention has been implicated as a causative factor in extracranial metastases (Beaumont et al 2007;Kalokhe et al 2012;Harrison et al 2016), but the findings of this study suggest the metastatic behavior observed was inherent to the disease progression rather than induced by therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The rarity of cases with extracranial metastases inhibits the elucidation of mechanisms underlying metastatic potential, but studies have suggested that physical barriers inherent to the intracranial environment, such as the dura mater, blood-brain barrier, and limited access to systemic circulation, contribute to the low occurrence of this phenomenon (Harrison et al 2016;Rosen et al 2018). Surgical intervention has been implicated as a causative factor in extracranial metastases (Beaumont et al 2007;Kalokhe et al 2012;Harrison et al 2016), but the findings of this study suggest the metastatic behavior observed was inherent to the disease progression rather than induced by therapy. Temozolomide has been found to induce hypermutation and treatment resistance in recurrent tumors (Hunter et al 2006), but the negligible activity of the TMZ-associated mutational signature in all samples implies that TMZ treatment did not significantly affect the mutational burden of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Several theories have been proposed as possible routes and mechanisms of such metastatic spread but, despite all the theories and evidence, such metastasis by gliomas is still a poorly understood process. Historically, it has been postulated that the lack of lymphatic vessels in the CNS constitutes a barrier to tumor spread [4, 7, 8, 13, 15, 18, 19]. However studies done in the last few years have highlighted the presence of a robust surrogate for a lymphatic system within the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…identified the presence of circulating tumor cells (CTC) in the peripheral blood in 29 of 141 patients with GBM by immunostaining of enriched mononuclear cells with antibodies directed against GFAP, thus demonstrating hematogenous dissemination of glioma cells [15]. The concept of CTCs has also been mentioned in a few other studies [8, 13, 14]. The hematogenous route is the main pathway for metastases to lung, bone, and spleen [7].…”
Section: Discussionmentioning
confidence: 99%
“…The tumor was malignant in terms of cell structure and had numerous mitotic divisions with necrosis, which causes rapid growth and metastasis to the surrounding tissue. 1,3 The spread of GBM to the extracranial area is rare, only seen in 0.4 to 2% cases. The spread of the tumor is often to the lungs, pleural cavity, chest, and lymph nodes and, less frequently, to bone and liver.…”
Section: Introductionmentioning
confidence: 99%